Effect of counterions on the binding affinity of Na+ ions with phospholipid membranes. Issue 87 (5th September 2016) - Maity, Pabitra; Saha, Baishakhi; Kumar, Gopinatha Suresh; Karmakar, Sanat
Abstract : We have systematically investigated the effect of counterions on the interaction of the Na + ion with phospholipid membranes using dynamic light scattering, zeta potential, isothermal titration calorimetry and fluorescence spectroscopy techniques. Abstract : We have systematically investigated the effect of counterions on the interaction of the Na + ion with phospholipid membranes using dynamic light scattering, zeta potential, isothermal titration calorimetry and fluorescence spectroscopy techniques. As model membranes, large unilamellar vesicles (LUV) have been prepared using an extrusion method and their size distribution confirmed using dynamic light scattering. The zeta potential of LUV in the presence of different sodium salts has been estimated from the measured electrophoretic mobility. The intrinsic binding constant of Na + in the presence of various counterions, such as Cl −, Br −, and I − was derived from the zeta potential using Gouy–Chapman theory at moderate salt concentrations (10–100 mM). The apparent binding constant estimated from ITC is in agreement with that obtained from the zeta potential. The overall endothermic response of binding heat suggests that the ion–membrane interaction is primarily entropy driven. The entropy gain might arise due to release of water molecules from the hydration layer vicinity of the membranes. The effect of counterions on the binding affinity of Na + follows the order I − > Br − > Cl − for neutral DOPC membranes. However, for negatively charged membranes, the order is Br − > I − > Cl − . The results of fluorescence spectroscopy also compliment the zeta potential and ITC results. Fluorescence lifetime and anisotropy experiments suggest that among all anions I − adsorbs and penetrates into the membrane, indicating a significant effect of the I − ion compared to other anions. Our result is in agreement with the earlier simulation study on this system.